Associations of depression and anxiety with substance use and social health among older adults living with HIV - Sarah Soliman (New Prairie Press, 2019)
Life expectancy after HIV infection dramatically increased following the development of antiretroviral therapies (ART) in 1996. As the population of older adults living with HIV increases, concerns have grown about possible disparities in mental health. We evaluated mental health outcomes, specifically depressive symptoms and anxiety, among older adults living with HIV in two large urban cities. We also examined the relationship between mental health outcomes and substance use and social health. We recruited 154 participants from infectious disease clinics in Los Angeles, CA and New Orleans, LA to complete cross-sectional surveys. We assessed prevalence of depressive symptoms (CES-D-10) and anxiety (GAD-7). Bivariate analyses and multivariate linear regressions were run to examine the factors associated with depressive symptoms and anxiety. We found that 44.8% of all participants were at risk for clinical depression, 55.8% reported mild to severe levels of anxiety, and 40.0% met criteria for both. In multivariate analyses, greater depressive symptoms and anxiety were associated with greater perceived HIV-related stigma and smaller social networks. Depressive symptoms were additionally associated with younger age. Substance use was not associated with depressive symptoms or anxiety. Findings suggest older adults living with HIV may be at high risk for depression and anxiety and that the presence of these conditions may also be linked to poorer social health indicators. This highlights the importance of screening for and addressing depression and anxiety among older adults with HIV.